Kajian Deskriptif Tentang Ontologi, Epistemologi, dan Aksiologi Dalam Filsafat Ilmu - Herman, Pebriani Yusnia; Karneli, Yeni; Handayani, Puji Gusri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This descriptive study aims to conceptually examine the three fundamental dimensions of the philosophy of science: ontology, epistemology, and axiology. These three aspects serve as the philosophical foundation for constructing a coherent scientific framework. Ontology explores the nature of existence and the boundaries of scientific inquiry; epistemology investigates the sources, methods, and validity of knowledge; while axiology examines the values and purposes of science, including ethical considerations and its utility for human life. This research employs a library research method by analyzing both classical and contemporary philosophical literature. The study finds that integrating these three dimensions is essential to ensure that the development of scientific knowledge is not only methodologically valid but also morally responsible and socially beneficial.